การประยุกต์ใช้งานสายอากาศโมโนโพลสำหรับระบบควบคุมความชื้นอัตโนมัติ ในโรงเรือนเพาะเห็ด - Leekul, Prapan (Naresuan University Journal: Science and Technology (NUJST); Vol 26 No 1 (2018): January - March 2018, 2018)
ระบบควบคุมความชื้นอัตโนมัติภายในโรงเรือนเพาะเห็ดใช้การวัดความชื้นจากการรับและส่งคลื่นความถี่ด้วยสายอากาศโมโนโพลรูปสี่เหลี่ยมผืนผ้าบนแผ่นวงจรพิมพ์ชนิด FR4 วิเคราะห์ความแตกต่างของกำลังงานจากคลื่นเดินทางผ่านอากาศที่มีความชื้นภายในโรงเรือนเพาะเห็ด สำหรับตัดสินใจให้ระบบทำการฉีดพ่นละอองน้ำให้กับโรงเรือน เพื่อให้ความชื้นเหมาะสมต่อการเจริญเติบโตของเห็ดนางฟ้าตลอดเวลา ระบบควบคุมความชื้นที่สร้างขึ้นทำงานที่ความถี่ 915 เมกะเฮิรตซ์ ประกอบด้วยภาคส่งและภาครับติดตั้งอยู่ตรงข้ามกันตามแนวยาวของโรงเรือนต้นแบบ ภาคส่งสร้างจากอุปกรณ์สังเคราะห์ความถี่ที่ถูกควบคุมด้วยอุปกรณ์ลอจิกแบบโปรแกรมได้ สัญญาณความถี่ที่สร้างขึ้นถูกขยายด้วยวงจรขยายกำลังงานและส่งผ่านสายอากาศ ภาครับแปลงสัญญาณความถี่เป็นแรงดันไฟฟ้ากระแสตรงและขยายให้ข้อมูลชัดเจนก่อนประมวลผลและตัดสินใจปรับความชื้นให้เหมาะสำหรับเห็ดนางฟ้าคือ 70% - 80% ผลการทดสอบควบคุมความชื้นในโรงเรือนจากระบบที่สร้างขึ้นตั้งแต่เวลา 6.00 น. ถึง 18.00 น. พบว่าค่าความชื้นอยู่ในช่วง 74.9% - 77.5% ซึ่งเป็นความชื้นที่เหมาะสมต่อการเจริญเติบโตของเห็ดนางฟ้า      This paper presents an automatic humidity control system in Sajor-caju mushroom growing house by using the transmitted and received RF signal from rectangular monopole antennas which are fabricated on FR4 substrate printed circuit board. An analysis of power variation from a travelling wave of the humid air in the mushroom growing house is used to control a water spray system to keep the humidity for the Sajor-caju mushroom. The built-in humidity control system operates at a frequency of 915 MHz, consisting of the transmitter and receivers. Both of antennas are installed across the length of the mushroom growing house. The transmission part is a synthesizer controlled by a field programmable logic gate array. The signal is amplified by power amplifier before sending to the transmitting antenna. At the receiver, the electromagnetic wave is converted to DC voltage and then it is amplified in order to use as the utilize data of the water spray in mushroom growing house. The DC voltages from humidity level of 70% - 80% are determined as a threshold value for the decision. The experiment of the humidity control of the mushroom growing house was tested from 6 am to 6 pm. From the measured results, it is showed that the humidity has the range from 74.9% to 77.5%, which is in the range of the appropriate humidity for the mushroom growing house.
Keywords: เซนเซอร์ไมโครเวฟ สายอากาศโมโนโพล ควบคุมความชื้น เห็ดนางฟ้า